DESKRIPSI PENGETAHUAN DAN INDEKS DMF-T DALAM RANGKA PENCEGAHAN MASALAH KESEHATAN GIGI DAN MULUT PADA SISWA BINA TALENTA GRAHA HARAPAN INDAH BEKASI - drg. M. Indriani Oktaria Sp.Pros (Mitramas: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The health of school students is part of the health development and prevention program by the Ministry of Health Republic of Indonesia.  Improvement of general health will affect oral health.  Prevention of oral health problems for Bina Talenta Graha students ranged from DMF-TT intraoral examination, dental health education, pre-test and post-test 33questionnaires, and mass toothbrushing activities. 44 kindergarten and 227 elementary school students participated in the program. DMF-T index was categorized according to WHO, in which the index for kindergarten is medium (3.92), while for elementary school classes is very high (8.7). Caries in both classes were more prevalent in girls than boys. The average score for kindergarten was 97.89 (pre-test) and 95.95 (post-test), while that of elementary school was 69 (pre-test) and 66.50 (post-test). Statistical tests for pre- and post-test yielded p = 0.623. for kindergarten and p= 0.151 for primary school. As p>0.05, there was no significant difference between pre- and-post tests for both groups. The decline in scores can be caused by short duration of dental health education, pre-, and post-tests. Environmental factors such as noise, visual disturbances, fatigue, and uncomfortable room conditions also played a role. By considering those factors, next activites can be planned and done more optimally